Physiological, Ecological, and Biochemical Implications in Tomato Plants of Two Plant Biostimulants: Arbuscular Mycorrhizal Fungi and Seaweed Extract - González-González, Mario Felipe; Ocampo-Alvarez, Héctor; Santacruz-Ruvalcaba, Fernando; Sánchez-Hernández, Carla Vanessa; Casarrubias-Castillo, Kena; Becerril-Espinosa, Amayaly; Castañeda-Nava, José Juvencio; Hernández-Herrera, Rosalba Mireya (Frontiers in Plant Science, 2020)
The worldwide use of plant biostimulants (PBs) represent an environmentally friendly tool to increase crop yield and productivity. PBs include different substances, compounds, and growth-promoting microorganism formulations, such as those derived from arbuscular mycorrhizal fungi (AMF) or seaweed extracts (SEs), that are used to regulate or enhance physiological processes in plants. This study analyzed the physiological, ecological, and biochemical implications of the addition of two PBs, AMF or SE (both alone and in combination), on tomato plants (Solanum lycopersicum L. cv. ‘Rio Fuego’). The physiological responses evaluated were related to plant growth and photosynthetic performance. The ecological benefits were assessed based on the success of AMF colonization, flowering and resistance capacity: non-photochemical quenching; NPQ, and polyphenol content. Biochemical effects were evaluated via protein, lipid, carbohydrate, nitrogen, and phosphorous content. Each PB was found to benefit tomato plants in a different but complementary manner. AMF resulted in an energetically expensive (high ETRMAX but low growth) but protective (high NPQ and polyphenol content) response. AMF + nutritive solution (NS) induced early floration but resulted in low protein, carbohydrate, and lipid content. Both AMF and AMF + NS favored foliar instead of root development. In contrast, SE and SE + NS favored protein content and root instead of foliar development with no flowering promotion. However, the combination of both PBs (AMF + SE) resulted in an additive effect, reflected in an increase in both foliar and root growth as well as protein and carbohydrate content. Moreover, a synergistic effect was also found, which was expressed in accelerated flowering, and AMF colonization. We present evidence of benefits to plant performance (additive and synergistic) due to the interactive effects between microbial (AMF) and non-microbial (SEs) PBs and propose that the complementary modes of action of both PBs may be responsible for the observed positive effects due to the novel or emergent properties of their constituents and not as an exclusive consequence of known components. These results will be an important contribution to biostimulant research and to the development of a second generation of PBs in which combined and complementary mechanism may be functionally designed.